Systematic revision of Central American Calligrapha Chevrolat of the subgenus Erythrographa subgen. nov. (Coleoptera: Chrysomelidae, Chrysomelinae) - Gómez-Zurita, Jesús (Zootaxa, 2018)
In this work, I revise a group of thirteen species in a natural assemblage of Calligrapha Chevrolat previously shown to represent a distinct and highly divergent lineage relative to other Calligrapha. The group is given subgeneric status, under the name Erythrographa subgen. nov., based on the morphological features of its representatives, which include reddish testaceous color to dark parts of body, including elytral markings, the presence of two spots enclosed by the humeral lunule, and a bifid end of the flagellum in male genitalia, among other typical features. One of the species of the new subgenus is also new and formally described as Calligrapha synthesys sp. nov. All the species of the subgenus Erythrographa subgen. nov. are found in Mexico (with the exception of C. wickhami, only known from southern Texas), with five species with larger distributions, reaching Nicaragua (C. notatipennis Stål), Costa Rica (C. labyrinthica Stål) or Panama (C. suboculata Stål, C. synthesys sp. nov. and C. tortilis Stål). The subgenus can be considered Neotropical, endemic of Central America and particularly diverse in the Mexican Transition Zone, between the Nearctic and Neotropical realms.